Evaluation of Radiographic, Neuropathological, and Demographic Findings in Children Aged 1 To 18 Years with Brain Tumor - Saket, Sasan; Nilipour, Yalda; Taherian, Reza; Fattahi Marnaanni, Niloufar (Novelty in Biomedicine, 2024)
Background: Brain tumors in children can involve different parts of the brain and cause high mortality. These tumors have different types, and they cause different conflicts and complications. So far, limited studies have been conducted in Iran on children's brain tumors. This study aimed to evaluate radiographic, neuropathological, and demographic findings in children aged 1 to 18 years with brain tumors. Materials and Methods: In this descriptive study, which was conducted for children aged 1 to 18 years with brain tumors admitted to the children's ward of Shohada Hospital (Iran-Tehran) in 2012-2018, 64 children were evaluated. Patient information was extracted from patients' files, including basic data radiological and clinical findings. A significance level was considered less than 0.05. Results: Twenty-six patients (40.6%) were girls, and 38 (59.4%) were boys. 96.9% of the children were term, and the mortality rate was 40.6%. 57.8% were diagnosed in less than one month from the onset of symptoms. 47.6% of patients had a positive family history, and none of them had a history of brain infection. The most common clinical complaint was N/V. The most common location of the tumor was the fourth ventricle (31.3%), and acute hydrocephalus was also seen in 19 patients (29.7%). The most common tumor was medulloblastoma (93.8%), and the most common stage was grade 4 (98.4%). Desmoplastic medulloblastoma was the most common form of medulloblastoma. 9.4% of patients were positive for tumor marker P53. None of the patients were positive for Beta-Catenin. Conclusion: The findings have shown that being a boy, involvement of the fourth ventricle and medulloblastoma are the most common characteristics of brain tumor involvement in Iranian children.